Implementasi Sharia Compliance Supervision di BPRS Amanah Sejahtera Gresik - Amin, Rukhul; Abdul Mujib (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research aims to answer the question regarding how to implement sharia compliance supervision at BPRS Amanah Sejahtera Gresik. The type of research used is field research using qualitative methods with a prospective case study approach (Prospective Case Study) and described descriptively. The research results obtained show that sharia supervision at BPRS Amanah Sejahtera Gresik is generally carried out in 2 ways. First, every new product/activity that will be launched. Second, supervision is also carried out on products/activities that have been launched. Both forms of supervision are carried out in several stages which have been adapted to applicable regulations